Rhythm on Your Lips - Peña, Marcela; Langus, Alan; Gutiérrez, César; Huepe-Artigas, Daniela; Nespor, Marina (Frontiers in Psychology, 2016)
The Iambic-Trochaic Law (ITL) accounts for speech rhythm, grouping of sounds as either Iambs—if alternating in duration—or Trochees—if alternating in pitch and/or intensity. The two different rhythms signal word order, one of the basic syntactic properties of language. We investigated the extent to which Iambic and Trochaic phrases could be auditorily and visually recognized, when visual stimuli engage lip reading. Our results show both rhythmic patterns were recognized from both, auditory and visual stimuli, suggesting that speech rhythm has a multimodal representation. We further explored whether participants could match Iambic and Trochaic phrases across the two modalities. We found that participants auditorily familiarized with Trochees, but not with Iambs, were more accurate in recognizing visual targets, while participants visually familiarized with Iambs, but not with Trochees, were more accurate in recognizing auditory targets. The latter results suggest an asymmetric processing of speech rhythm: in auditory domain, the changes in either pitch or intensity are better perceived and represented than changes in duration, while in the visual domain the changes in duration are better processed and represented than changes in pitch, raising important questions about domain general and specialized mechanisms for speech rhythm processing.